Mosty zamiast barier: Literaturoznawstwo a psychologia – o relacjach i współzależnościach - Całek, Anita (Księgarnia Akademicka Publishing, 2024)
BRIDGES INSTEAD OF BARRIERS: LITERARY STUDIES AND PSYCHOLOGY – ABOUT REATIONS AND INTERDEPENDENCIES The relationship between psychology and the study of literature seems paradoxical. On the one hand, these fields do not have much in common, neither in terms of the subject of research, nor in terms of methodological or theoretical aspects. They have separate discourses, deeply rooted in the traditions of their own disciplines and obtaining their scientific validation there. On the other hand, it is difficult not to notice common research interests, especially in the field of creativity, biographical research or literary texts themselves, which are taken up by both literary scholars and psychologists, although they do it less often. The search for a universal language of the humanities in the 20th century ended in failure and the final separation of sciences, and then – further specialisation, which today makes communication and cooperation between disciplines difficult. At the core of this monograph is the idea to build bridges to facilitate understanding and implementation of specific research projects. Therefore, it is not about understanding in general, but about seeking cooperation and coexistence around specific problems that are worth analysing together, and not separately. This is the basic message of the book: bridges are better than barriers because they allow us to jump over the walls that separate particular fields from each other and look for understanding, the foundations of which are relationships based on mutual respect, empathy and partnership cooperation. The whole book consists of sixteen chapters, quite diverse, although connected by common threads, gathered around four overarching ideas, important in terms of interdisciplinarity, which are: relationships, biography, creator and literature. In these areas, it was possible to build a space for coexistence and cooperation between literary studies and psychology in theory and in the process of interpretation (the fourth chapter of each part is devoted to practical testing of the possibilities of such cooperation in relation to a specific research challenge).